Behavioural crypsis in a South African galaxiid fish induced by predatory and non‐predatory heterospecifics. Issue 5 (4th September 2019) - Magellan, Kit
Abstract: This study investigated recognition of, and behavioural responses to, predatory and non‐predatory heterospecifics by a small cryptically coloured fish species, Galaxias 'nebula'. Nebula recognised and differentiated between predatory and non‐predatory heterospecifics and altered its behaviour facultatively. With both predatory and non‐predatory fishes, the proportion of time spent motionless increased, whereas refugia use was affected only by predators and neither heterospecific affected the time spent active. Although nebula appeared to face no conflict, in that their responses to predatory and non‐predatory heterospecifics varied in the same direction and differed only in intensity, the presence of both heterospecifics together induced responses midway between those for each heterospecific separately. Non‐predatory heterospecifics thus modified nebula's responses towards predators, potentially making time available for other essential activities such as foraging. This modified predator response may aid its survival in an increasingly threatened habitat.